MEDIA SI ODIK STOCOPIC UNTUK MENGURANGI BUDAYA MENGHAFAL UNSUR KIMIA SISTEM PERIODIK - Melisa, Mey; Herlina, Endang; Syafitri, Diah; Bella, Riska (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The background of this article is come up from the problem in chemistry learning process for senior high school exactly about the foundation of chemistry which is periodic table. The aimed of this research is to find out the influence of Si Odik Stocopicâs medium to minimize the memorizingâs way in periodic table chemistry material. The method that used in this research is Quasi Experiment Design with Nonequivalent Control Group Design type, with the studentâs group sample which is divided into control class and treatment class by random way. The research was held in even semester students of 2013-2014 during one month in private school of SMA IT Raudhatul Ulum Sakatiga, Indralaya. The result from this research is proved that using medium of Si Odik Stocopic was totally optimize the use right brain, indeed, it will increase the studentâs understanding, studentâs ability memory for chemistry lesson and also to minimize the memorizingâs way in chemistry learning process.Â Keywords: Â Medium of Si Odik Stocopic, Right Brain, Element Periodic System